Integrating Instagram into Arabic Vocabulary Instruction: A Study on Interactive Learning in Higher Education - Linur, Rahmat; Supriani, Ria Rafita (Institut Agama Islam Negeri Palangka Raya, 2025)
This study investigates the effectiveness of Instagram as an innovative medium for enhancing Arabic vocabulary mastery among university students in Islamic higher education. Despite the growing integration of digital tools in education, vocabulary instruction in Arabic courses remains dominated by rote memorization and teacher-centered methods, often resulting in low motivation and limited retention. Instagram, popular among students, offers interactive and visual features that could support more engaging and flexible language learning, yet remains underexplored in this context. Focusing on students in the Natural Sciences Education Program at a State Islamic Institute in Indonesia, this study employs a descriptive qualitative approach. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman model involving data reduction, display, and verification. Findings show that Instagram enhances vocabulary learning through its accessibility, content variety, and alignment with student preferences. The platform fosters increased motivation, creativity, and engagement, while its visual and interactive nature supports vocabulary comprehension and retention. This study contributes to the field of technology-assisted Arabic instruction by addressing a gap in empirical research on social media use in Islamic higher education. It highlights the pedagogical potential of integrating familiar digital platforms like Instagram to support more autonomous and effective language learning.